Association between body mass index, metabolic syndrome and common urologic conditions: a cross-sectional study using a large multi-institutional database from the United States. (12th December 2023) - Suarez Arbelaez, Maria Camila; Nackeeran, Sirpi; Shah, Khushi; Blachman-Braun, Ruben; Bronson, Isaac; Towe, Maxwell; Bhat, Abhishek; Marcovich, Robert; Ramasamy, Ranjith; Shah, Hemendra N.
Abstract: Introduction: The study aims to determine whether body mass index (BMI), metabolic syndrome (MS) or its individual components (primary hypertension, type 2 diabetes mellitus and dyslipidemias) are risk factors for common urological diseases. Materials and methods: Cross-sectional study with data collected on February 28, 2022 from the TriNetX Research Network. Patients were divided in cohorts according to their BMI, presence of MS (BMI > 30 kg/m 2, type 2 diabetes mellitus, primary hypertension and disorders of lipoprotein metabolism) and its individual components and its association with common urological conditions was determined. For each analysis, odds ratio (OR) with 95% confidence intervals were calculated. Statistical significance was assessed at p  < .05. Results: BMI > 30 kg/m 2 was associated with increased risk of lithiasis, kidney cancer, overactive bladder, male hypogonadism, benign prostatic hyperplasia, and erectile dysfunction ( p  < .05). On the contrary, BMI was inversely associated with ureteral, bladder and prostate cancer ( p  < .05). In all urological diseases, MS was the strongest risk factor, with prostate cancer (OR = 2.53) showing the weakest and male hypogonadism the strongest (OR = 13.00) associations. Conclusions: MS and its individual components were significant risk factors for common urological conditions. Hence holistic approaches with lifestyle modification might prevent common urological disease. Key messages: Overall, metabolic syndrome is the strongest risk factor for all the analysed urological diseases. Abnormally high body mass index can be a risk or protective factor depending on the threshold and urological disease that are being evaluated. Metabolic syndrome and increased BMI should be considered important factors associated to the prevalence of common urological diseases.